Advances in service-oriented and cloud computing : workshops of ESOCC 2017, Oslo, Norway, September 27-29, 2017, revised selected papers /: workshops of ESOCC 2017, Oslo, Norway, September 27-29, 2017, revised selected papers. (2018) - Unknown
No abstract available